Transforming Wounds into Words: Violence, Trauma, and Memory in Rana’s Seto Bagh and Rushdie’s The Knife - Ghimire, Sushil (Mindscape: A Journal of English & Cultural Studies, 2024)
Literature offers a vital space to confront violence, preserve memory, and reimagine survival. Diamond Shumsher Rana’s Seto Bagh (1973; The White Tiger, 1991) dramatizes the disintegration of the Rana regime, exposing political betrayal, systemic brutality, and the precariousness of dynastic authority. Salman Rushdie’s The Knife (2024), composed after an assassination attempt, shifts the focus to an intimate register, meditating on bodily trauma, resilience, and the endurance of voice in the face of censorship and extremism. Though divergent in genre and context—historical fiction and memoir—both works trace the persistence of trauma and its return through memory and narration. Grounded in Cathy Caruth’s trauma theory, this study examines how Rana and Rushdie differently translate violence into narrative: Seto Bagh memorializes collective suffering, framing political collapse as historical inevitability, while The Knife testifies to lived vulnerability, underscoring survival and artistic defiance. Reading these texts together reveals literature’s dual role as archive and testimony—one that preserves communal histories of violence and bears witness to individual endurance. Ultimately, both works affirm that trauma, whether national or personal, demands articulation. In transforming wounds into words, they resist silencing forces and ensure that memory remains a living act of resistance.